Pengaruh Dana Pihak Ketiga dan Non-Performing Loan terhadap Penyaluran Kredit pada Bank yang Terdaftar di BEI - Popy Sandra Tesalonica Hutahaean; Diharpi Herli Setyowati; Endang Hatma Juniwati (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
The purpose in this research was to find the effect of third party funds and non-performing loans on the amount of lending to banking sector listed on the Indonesia Stock Exchange for the period 2014 to 2018. The research method used is quantitative descriptive method. The data used are secondary data in the form of annual financial reports, and the data analysis technique uses multiple linear regression analysis. The data processing in this study used a statistical tool, namely E-views 9. The results of this study indicate that partially third party funds have a positive and significant effect on the amount of lending and non-performing loans have a negative and significant effect on the amount of credit disbursement. Simultaneously or together, third party funds and non-performing loans have a significant effect on the amount of lending.